A Study of the Interaction Between Implanted Pacemakers and the Power-Frequency Field Produced by Traction Transformer in High-Speed EMU - Rui Tian; Yu-Long Zhang; Mai Lu; Jian-Fang Deng (IEEE Access)
The widespread integration of high-speed trains has significantly enhanced the quality of human life. However, the intricate electromagnetic environment within carriages has raised notable concerns, especially for passengers with pacemakers. This work assessed the electromagnetic exposure of three-chamber pacemaker wearers with standed and seated posture by a traction transformer and its cable system. The analysis included evaluating the distribution of induced electromagnetic fields within passengers’ pacemakers and heart tissue, calculating the induced voltage on electrodes to determine the potential health risks. The results indicated that the B $_{in~max}$ , E $_{in~max}$ of the passengers’ heart tissue are $7.53~μ $ T and 47.626 mV/m. All the B $_{in~max}$ , E $_{in~max}$ well within the basic limits established for public electromagnetic exposure set by the International Commission on Non-Ionizing Radiation. The Ein on the pacemakers of both passengers mainly appeared at the metal parts, and the B $_{in~max}$ of passengers’ pacemakers is $20.754~μ $ T, which achieves the minimum requirements for pacemakers to anti-electromagnetic interference as specified by the International Organization for Standardization. The $U_{in~max}$ at the unipolar and bipolar electrodes of passengers are 0.409 mV and 0.005 mV, which are smaller than the perception sensitivity. The above results illustrated that the electromagnetic fields generated by the traction transformer are within the recognized accepted limits for passengers with pacemaker, and we recommended that individuals with heart diseases should try to choose a pacemaker with better anti-interference ability in bipolar pacing mode and keep a distance from windows as possible when riding on high-speed trains.